APAKAH MANAJEMEN LABA MERUSAK PRINSIP TRANSPARANSI DAN AKUNTABILITAS INFORMASI KEUANGAN? - Maharany, Griselda Ladyonna; Oktavia, Reni (Universitas Triatma Mulya, 2024)
The practice of earnings management is carried out by companies to present financial reports that are appealing to stakeholders. However, some manipulations conducted in the context of earnings management are feared to compromise the transparency and accountability principles of financial reporting. The differing definitions of earnings management presented by experts also contribute to making this topic controversial. This literature review aims to elucidate and re-examine the practices of earnings management and perspectives from both sides: the proponent side supporting earnings management practices and the opposing side rejecting the implementation of earnings management in companies. The review's findings indicate that earnings management practices can be supported through the implementation of fraud prevention measures aimed at preserving these practices to continue operating within the confines of financial accounting standards.